What explains month-end funding pressure in Canada? - Christopher S. Sutherland (Bank of Canada, 2017)
The Canadian overnight repo market persistently shows signs of latent funding pressure around month-end periods. Both the overnight repo rate and Bank of Canada liquidity provision tend to rise in these windows. This paper proposes three non-mutually exclusive hypotheses to explain this phenomenon. First, month-end funding pressure may be caused by search frictions. Market participants place a premium on liquidity around month-end periods because of the confluence of a generalized liquidity preference, heightened month-end forecast uncertainty, and resultant search frictions in the repo market. Second, this funding pressure could be attributed to spillovers from the US overnight repo market. Third, month-end funding pressure might be associated with large Canadian banks' end-of-month repo adjustments. By combining market, central-bank and payments data, this paper provides evidence that the first hypothesis explains the latent funding pressure observed on the first day of the month. Using market and non-public regulatory data, this paper further argues that the second and third hypotheses are much less plausible.
Keywords: E41; E43; E52; E58; F36; G15; G14; G21; 330; Interest rates; Financial markets; Monetary policy implementation; Monetary policy framework; Transmission of monetary policy